2021
DOI: 10.1002/lsm.23384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artesunate Combined With Fractional CO2 Laser on the Hypertrophic Scar in a Rabbit Model

Abstract: Background and ObjectivesHypertrophic scar (HS), a common complication in wound healing, is characterized by the disarrangement of collagen, fibers, and extracellular matrix. Artesunate (ART) can inhibit the abnormal formation of fibroblasts and collagens. Fractional CO2 laser (FCO2L) can facilitate tissue remodeling and the absorption of drugs into ablative microthermal columns in HS. So far, no research has investigated the efficacy of ART combined with an FCO2L in treating HS. To investigate the theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Among them, the animal scar model is one of the important methods to study pathological scar at present. The commonly used animal scar models include traditional animal scar models, such as the rodent model, rabbit ear model, and porcine model; however, none of these animal scar models can perfectly simulate the pathological scar formation and healing process of humans 37,38 . The rapid development of new technologies such as in vitro transplantation technology, transgenic technology, and tissue engineering technology also provides new ideas and strong support for the construction of scar model 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the animal scar model is one of the important methods to study pathological scar at present. The commonly used animal scar models include traditional animal scar models, such as the rodent model, rabbit ear model, and porcine model; however, none of these animal scar models can perfectly simulate the pathological scar formation and healing process of humans 37,38 . The rapid development of new technologies such as in vitro transplantation technology, transgenic technology, and tissue engineering technology also provides new ideas and strong support for the construction of scar model 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used animal scar models include traditional animal scar models, such as the rodent model, rabbit ear model, and porcine model; however, none of these animal scar models can perfectly simulate the pathological scar formation and healing process of humans. 37 , 38 The rapid development of new technologies such as in vitro transplantation technology, transgenic technology, and tissue engineering technology also provides new ideas and strong support for the construction of scar model. 39 Organs‐on‐chips, which have been widely used in organ and disease models, are highly likely to be used to construct scar models in vitro in future.…”
Section: Discussionmentioning
confidence: 99%
“…A further subgroup analysis was also performed which revealed that patients at the early stage could experience more significant improvement after the treatment of combined therapy. Ablative fractional CO 2 laser technology has been employed for many years; however, it is only in recent years that this technique has been applied to the treatment of hypertrophic scars (3,4,(13)(14)(15)(16)(17)(18)(19). Several case reports firstly reported the effectiveness of ablative fractional CO 2 laser treatment for hypertrophic scars (20,21), then Makboul et al enrolled 40 patients with hypertrophic scars and confirmed ablative fractional CO 2 laser treatment as a feasible management for hypertrophic scarring (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effectiveness of CO 2 lasers (a fractional CO 2 laser, in particular) for the treatment of epithelial scars from trauma, surgical wounds and acne was reported in clinical studies using biopsy samples [5][6][7][8][9], in studies using a scar scale or a visual analog scale [10][11][12][13][14][15][16] and in basic studies using experimental animals [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%